Pendampingan Pengelolaan Dan Pemanfaatan Informasi Keuangan UMKM Di Dusun Ngembes, Mojokerto: Indonesia - Mienati Somya Lasmana; Permatasari, Yani; I Made Narsa; Erina Sudaryati; Wiwiek Dianawati; Murdiyati Dewi; Hamidah; Elia Mustikasari; Alfiyatul Qomariyah; Okta Shindu Hartadinata; Deddy Kurniawansyah (Fakultas Ekonomi, Universitas PGRI Adi Buana Surabaya, 2025)
This Community Service program was conducted in Dusun Ngembes, Mojokerto, involving 11 instructors and engaging 30 MSME (Micro, Small, and Medium Enterprise) actors. The program focused on two primary issues: (1) improving the knowledge and skills of MSME managers in managing and preparing financial reports, which remain suboptimal, and (2) addressing the limited use of financial information for business growth. The program employed methods such as interviews, lectures, tutorials, discussions, and direct field observations to comprehensively explore MSME management practices. Data analysis was performed using a descriptive analytical approach to generate actionable recommendations. The outcomes aimed to enhance participants' capabilities in financial management, with an emphasis on accurate cost calculation to boost profitability. Ultimately, this program sought to empower MSMEs with the tools and insights needed to achieve sustainable business development and improve their overall welfare